WOMAN AND LEADERS OF CONTEMPORARY SUFISM - Basmah Nafisah (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
The world of Sufism developed as part of an adaptive discursive tradition of socio-political conditions and external influences, so Sufism has a pluralistic style. This study explores contemporary Sufism and active involvement of women, both Muslim and non-Muslims in Sufi activities. The purpose of this study is to describe history, dynamics, and the influence of contemporary Sufism on gender issues and feminism in secular societies. The method used is qualitative research with a literature study approach, through literature analysis related to contemporary sufism. Meta-analysis techniques are used to connect various existing variables with more structured studies. Research shows that Sufism, despite being rooted in Islam, develops beyond religious normitality and emphasizes the search for universal spiritual meanings. In this context, contemporary Sufism allows women to go beyond the boundaries of Islamic normative dogma, find true meaning, and free to express themselves. Through Sufism, it is proven that religion can have a significant influence on modernity and respond to issues such as gender and equality. Women not only become followers in Sufi activities, but also become leaders in Sufi activities.